2021
DOI: 10.1111/jcpt.13363
|View full text |Cite
|
Sign up to set email alerts
|

Systematic external evaluation of reported population pharmacokinetic models of vancomycin in Chinese children and adolescents

Abstract: What is known and objectives: Various population pharmacokinetic (PopPK) models for vancomycin in children and adolescents have been constructed to optimize the therapeutic regimen of vancomycin. However, little is known about their predictive performance when extrapolated to different clinical centres. Therefore, the aim of this study was to externally validate the predictability of vancomycin PopPK model when extrapolated to different clinical centres and verify its applicability in an independent data set. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…However, there are only a few model studies on adult neutropenic patients (Joaguim et al, 2018). Jarkowski had developed a two-compartment model of vancomycin in hematologic patients in 2012 (Jarkowski et al, 2012), while other reports focus on children (Lv et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only a few model studies on adult neutropenic patients (Joaguim et al, 2018). Jarkowski had developed a two-compartment model of vancomycin in hematologic patients in 2012 (Jarkowski et al, 2012), while other reports focus on children (Lv et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the predictability of different popPK models when extrapolated to other clinical centers might remain to be compared ( Lv et al, 2021 ). An external validation study based on published VPA models by Zang et al (2022b) suggested that the absence of children, Asian ethnicity, one-compartment models, and inclusion of the covariates body weight (BW) and VPA dosage, were the most important factors contributing to good performance in their Chinese dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the predictability of different popPK models when extrapolated to other clinical centers might remain to be compared (Lv et al, 2021). An external validation study based on published VPA models by Zang et al (2022b) suggested that the absence of children, Asian ethnicity, onecompartment models, and inclusion of the covariates body weight (BW) and VPA dosage, were the most important factors contributing to good performance in their Chinese dataset.…”
Section: Data Source and Dataset Constructionmentioning
confidence: 99%